Increase of electronegative-LDL-fraction ratio and IDL-cholesterol in chronic kidney disease patients with hemodialysis treatment - Hirowatari, Yuji (BioMed Central, 2012)
BACKGROUND: It is known that the increased level of IDL and oxidized LDL are associated with risk of cardiovascular disease, and the lipoprotein abnormalities accelerate atherosclerosis. Cardiovascular disease is a major cause of mortality in chronic kidney disease patients with hemodialysis treatment (HD-Ps). Therefore, the estimation of lipoprotein profiles is important for prevention of cardiovascular disease in HD-Ps. We previously established an anion-exchange chromatographic method for measurement of cholesterol level in subclasses of HDL and LDL, IDL, VLDL, and chylomicron. An electronegative-LDL-fraction contained minimally oxidized-LDL. Lipoprotein profile can be accurately and conveniently determined by the new method. FINDING: In this study, lipoprotein profiles in HD-Ps and age-matched healthy subjects were estimated by using our established anion-exchange chromatographic method. The ratio of electronegative-LDL-cholesterol to total LDL-cholesterol and IDL-cholesterol in HD-Ps were significant higher than those in healthy subjects. CONCLUSIONS: The results suggest that the ratio of electronegative-LDL-cholesterol to total LDL-cholesterol and IDL-cholesterol obtained by the new method may serve as useful markers for risk of cardiovascular disease in HD-Ps.